Genetic relationship of galangal (alpinia galanga Willd.) in Thailand by RAPD analysis - O. Saritnum (2018)
The genetic relationship of galangal (Alpinia galanga Willd.) accessions collected from northern, central, eastern, and northeastern districts of Thailand was investigated by cluster analysis based on random amplified polymorphic DNA (RAPD) markers. In addition, a RAPD marker linked to 1'- acctoxychavicol acetate (ACA) content, one of the most important characters of galangal, was explored with a view to breeding high ACA content cultivars. Eight 10-mer random primers amplified 73 polymorphic RAPD bands and a dendrogram constructed by UPGMA method clustered 30 cultivated and 7 wild accessions into 5 major clusters. Large clusters I and II corresponded with geographical distribution and ACA content. Clusters I and II mainly consisted of accessions from northern and central districts, respectively. Although a wide variation of ACA content (0-7.5% w/dw) was observed, most of the high ACA content accessions clustered together in cluster II and accessions in cluster I had significantly lower ACA contents than the ones in cluster II. Four RAPD bands specific to high ACA accessions were found: 450 bp (OPB18), 800 bp (OPC09), and 450 bp, and 550 bp (OPAX17). These fragments are potential DNA markers for screening high ACA content accessions. Wild accessions did not cluster independently and were spread over three clusters with a wide variation of ACA content as the cultivated ones. Wild accessions having high ACA content are available as breeding materials for developing high ACA content cultivars.